User acceptance in a computer-supported collaborative learning (CSCL) environment with social network awareness (SNA) support - Lin, Jian-Wei; Lin, Hao-Chiang Koong (Australasian Journal of Educational Technology, 2019)
Although many e-learning studies have applied the unified theory of acceptance and usage of technology (UTAUT) to investigate user acceptance, their findings have been inconsistent. One of reasons is that the user acceptance model of an e-learning system can be determined by the new information technologies (or mechanisms) the e-learning system utilises. Computer-supported collaborative learning (CSCL) with social network awareness (SNA) mechanisms has been widely adopted because it can enhance online collaborative learning effectiveness. Since new SNA mechanisms are expected to have a huge impact on user acceptance in CSCL environments, this study extends UTAUT to investigate user acceptance of an SNA CSCL environment. This study empirically evaluated the extended model by surveying 186 undergraduates, who had completed a 5-week electric commerce course in an SNA CSCL environment. The findings indicated that the SNA mechanism substantially strengthened the effect of social influence on behavioural intention to use the SNA CSCL system. Compared with other CSCL studies, the predictive power of social influence in this study was higher, while that of other determinants (i.e., performance expectancy and effort expectancy) in this study were lower. The extended model demonstrated higher explanatory power compared to models used in other CSCL studies.